Bilateral Moyamoya disease resulting in anterior circulation stroke: first case report in Sri Lanka - T. Tharsiga; S. Yathukulan; P. Mayurathan (Asian Journal of Internal Medicine)
Bilateral Moyamoya disease is a rare vascular cause of young onset ischaemic stroke, characterised by progressive narrowing of the cerebral vessels. We present a case of a 28-year-old Sri Lankan man with a unilateral headache presenting with sudden onset of expressive aphasia without face, arm or leg weakness. Magnetic resonance imaging revealed evidence of multiple infarctions involving both left and right middle cerebral territories. The diagnosis was made based on the magnetic resonance angiography, which demonstrated the absence of supra clinoid segments of bilateral middle cerebral arteries (MCA) and the presence of significant collateral formation which are typical of Moyamoya disease. He was commenced on low dose aspirin, high intensity statin and speech therapy. He had a favourable outcome. Although a genetic component is commonly associated with Moyamoya disease, no such family history was identified and immunological, infectious, haematological, vascular, or congenital syndromes were not found. This is the first case of bilateral Moyamoya disease reported from Sri Lanka.